Influence of adapted hip-hop dancing on quality of life and social participation among children/adolescents with cerebral palsy - Joseana Wendling WITHERS; Sandra Baggio MUZZOLON; Marise Bueno ZONTA (Arquivos de Neuro-Psiquiatria)
ABSTRACT To describe the influence of adapted hip-hop dancing on the quality of life (QoL) and biopsychosocial profile of children/adolescents with cerebral palsy (CP). Methods Pilot study including 18 children/adolescents with CP and Gross Motor Function Classification System levels I and II. Nine participants took part in an adapted hip-hop dance practice (study group; SG), and nine others served as the control group (CG). All participants were assessed with the Pediatric Outcomes Data Collection Instrument and the Child Behavior Checklist at baseline and after at least three months of dance practice and a public performance (SG) or a similar period without intervention (CG). Results Improvement in QoL was observed in the SG in the domains of transfer and basic mobility (p = 0.00*), sporting and physical function (p = 0.04*), and global function and symptoms (p = 0.01*). In the SG, there was a reduction in emotional and behavioral problems and an increase in social competence in the biopsychosocial profile. Greater participation in adapted hip-hop dancing was associated with a greater gain in the transfer and basic mobility domains (p = 0.05*) of the Pediatric Outcomes Data Collection Instrument and in the activities (p = 0.05*) and social (p = 0.04*) scales of the Child Behavior Checklist. Conclusions Children/adolescents with CP participating in adapted hip-hop dance practice showed improvement in QoL and biopsychosocial profile scores.